Study Of Parametric Mismatch Of Supercapacitor Materials - et. al., Jaywant Suryawanshi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Since early 1980s, evolution in industrialization and rapid growth in population resulted in huge demands of automation and innovation in various sectors. One of the major innovations was energy storage systems. The present work is a research done on one of the modern-day energy storage devices i.e., Supercapacitor. Supercapacitor is an emerging energy storage device, and it has high potential to meet energy storage requirements for many applications in combination with batteries. Supercapacitors can be charged at faster rates and can deliver large output current. In this research, various components like electrodes, electrolytes, separators, and packaging materials are selected and tried to find the crux behind some of the issues in present day supercapacitor. This encapsulates various materials used in a supercapacitor, several parametric mismatches of the material used, and its impact upon capacitance value. This will help companies in manufacturing supercapacitors to select proper material having better characteristics.